Barangan Banana (Musa acuminata L.) Shoots Induction By Application Of NAA And BAP Based On The Sources Of Explant Basal - Hardi Yudha; Suci Rahayu; Saleha Hanum (Universitas Negeri Medan, 2015)
The research or barangan banana (Musa acuminata L.) shoot induction by application of NAA and BAP based on the source of explans basal that had been carried out in the system Culture Laboratory of the University of North Sumatra. This study aims to discover the source of explants forming shoots by application of NAA and BAP and the number of shoots formed by the application of NAA and BAP based sources of banana explants. The study uses a completely randomized design with two factorial, i.e. the concentration factor NAA (0 mg/l, 1.5 mg/l, 2.0 mg/l, 2.5 mg/l, and 3.0 mg/l) and concentration factor BAP (0 mg/l, 4 mg/l, 5 mg/l, 6 mg/l, and 7 mg/l) with the source explants apical and basal parts. The best position that created the shoots explants contained in explant basal part by the number of shoot formed is 83. In the treatment of 1.5 mg/l NAA and 5 mg/l BAP average number of shoots most 3,75 and 2,30 cm tall shoots, the formation of the shoots is in the 80th day. The application of NAA and BAP on basal explants have a significant influence on the formation of the shoots. Key words: Musa acuminata L., NAA, BAP,explants basal, shoot.